Transmission-blocking compound candidates against Plasmodium vivax using P. berghei as an initial screening - Camila Fabbri; Alexandre Oliveira Trindade; Francy’s Sayara Andrade; Macejane Ferreira de Souza; Claudia María Ríos-Velásquez; Marcus Vinicius Guimarães de Lacerda; Wuelton Marcelo Monteiro; Fabio Trindade Maranhão Costa; Rogerio Amino; Stefanie Costa Pinto Lopes (Memorias do Instituto Oswaldo Cruz, 2021)
BACKGROUND Different strategies for improvement of malaria control and elimination are based on the blockage of malaria parasite transmission to the mosquito vector. These strategies include the drugs that target the plasmodial sexual stages in humans and the early developmental stages inside mosquitoes. OBJECTIVES Here we tested Malaria Box compounds in order to evaluate their activity against male and female gametocytes in Plasmodium berghei, mosquito infection in P. vivax and ookinete formation in both species. METHODS/FINDINGS The membrane feeding assay and the development of ookinetes by a 24 h ex vivo culture and the ookinete yield per 1000 erythrocytes were used to test transmission-blocking potential of the Malaria Box compounds in P. vivax. For P. berghei we used flow cytometry to evaluate male and female gametocyte time course and fluorescence microscopy to check the ookinete development. The two species used in this study showed similar results concerning the compounds’ activity against gametocytes and ookinetes, which were different from those in P. falciparum. In addition, from the eight Malaria Box compounds tested in both species, compounds MMV665830, MMV665878 and MMV665941 were selected as a hit compounds due the high inhibition observed. CONCLUSION Our results showed that P. berghei is suitable as an initial screening system to test compounds against P. vivax.